2001
DOI: 10.1128/mcb.21.4.1024-1035.2001
|View full text |Cite
|
Sign up to set email alerts
|

Shared Pathways of IκB Kinase-Induced SCFβTrCP-Mediated Ubiquitination and Degradation for the NF-κB Precursor p105 and IκBα

Abstract: p105 (NFKB1) acts in a dual way as a cytoplasmic IB molecule and as the source of the NF-B p50 subunit upon processing. p105 can form various heterodimers with other NF-B subunits, including its own processing product, p50, and these complexes are signal responsive. Signaling through the IB kinase (IKK) complex invokes p105 degradation and p50 homodimer formation, involving p105 phosphorylation at a C-terminal destruction box. We show here that IKK␤ phosphorylation of p105 is direct and does not require kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
128
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 59 publications
(83 reference statements)
12
128
1
Order By: Relevance
“…These phosphorylations induce the binding of SCF βTrCP E3 ligase, which catalyzes the subsequent K48-linked polyubiqitination and proteolysis of p105 by the proteasome [42,44,45]. This predominantly leads to the complete degradation of p105, rather than processing to p50 [42,44]. As a consequence of signal-induced p105 degradation, associated Rel subunits are released to regu- Figure 3 Canonical pathway of NF-κB activation.…”
Section: Regulation Of Tpl-2 Signaling By Nf-κb1 P105mentioning
confidence: 99%
“…These phosphorylations induce the binding of SCF βTrCP E3 ligase, which catalyzes the subsequent K48-linked polyubiqitination and proteolysis of p105 by the proteasome [42,44,45]. This predominantly leads to the complete degradation of p105, rather than processing to p50 [42,44]. As a consequence of signal-induced p105 degradation, associated Rel subunits are released to regu- Figure 3 Canonical pathway of NF-κB activation.…”
Section: Regulation Of Tpl-2 Signaling By Nf-κb1 P105mentioning
confidence: 99%
“…Correlation analysis indicated that the mRNA levels of pro-inflammatory cytokines TNF-a, IL-1b, IL-8, IFN-g2 and IL-12p40 were positively correlated with the mRNA levels of NF-kB P65 and NF-kB P52 in the gills of grass carp ( Table 5). The nuclear translocation of NF-kB may be inhibited by IkBa in humans [69], and Heissmeyer et al [70] reported that the IKK complex (including IKKa, IKKb and IKKg) catalyses IkBa degradation in 293 cells. In the present study, compared with low or high levels of protein, we found that the optimal levels of dietary protein led to the down-regulation of IKKa, IKKb and IKKg mRNA levels and the up-regulation of IkBa mRNA level in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Resmentioning
confidence: 99%
“…However, wild-type p105 cannot be employed as an NF-B super repressor, because expression of the nfkb1 gene always produces both p105 and p50 in the cell, and the latter is a component of the NF-B transcription complex (23,24). In addition, wild-type p105, like I B␣, also undergoes signal-induced complete degradation, releasing the bound NF-B species into the nucleus (25). Compared with I 〉␣, however, p105 possesses important features that make it potentially a broader range NF-B super repressor.…”
mentioning
confidence: 99%
“…First, p105 interacts with all Rel proteins, including p50, p52, and RelB, with high affinity through the Rel homology domain (RHD) and I B␥-like ankyrin repeats. Second, although both require the proteasome activity, p50 biogenesis and p105 degradation are separate processes (23,(25)(26)(27)(28). The middle region of p105, which contains a glycine-rich region (29) and a putative degradation signal for the proteasome (30), is likely to be responsible for p50 generation.…”
mentioning
confidence: 99%